Session Topic: Recent Theoretical Developments in Financial Theory: Discussion - Willig, Robert (Journal of Finance, 1978)
Robert Willig, Session Topic: Recent Theoretical Developments in Financial Theory: Discussion, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 792-794